2020
DOI: 10.3390/cancers12092538
|View full text |Cite
|
Sign up to set email alerts
|

Orbital and Eyelid B-Cell Lymphoma: A Multicenter Retrospective Study

Abstract: Background: The aim of this study was to analyze patients diagnosed, staged and treated for orbital and eyelid B-cell lymphoma (OEL). Methods: One hundred and forty-one cases of OEL were included in this study. Primary endpoints were to analyze the histopathologic findings, the main risk factors and the type of treatment and to correlate them with recurrence of OEL. The secondary endpoint was to determine the progression-free survival (PFS) time. Results: Extranodal marginal zone B-cell lymphoma was the most f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…We found only a slightly MALT lymphoma predominance in general orbital lymphoma which is consistent with previous reports 2,11 . However, in other studies, especially from Asia, the incidence of MALT lymphoma was significantly higher, ranging from 66% to 82% of total orbital lymphoma 1,3,12,13 . Unexpectedly, among non‐MALT lymphoma, almost 30% of patients had diffuse large‐cell lymphoma.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We found only a slightly MALT lymphoma predominance in general orbital lymphoma which is consistent with previous reports 2,11 . However, in other studies, especially from Asia, the incidence of MALT lymphoma was significantly higher, ranging from 66% to 82% of total orbital lymphoma 1,3,12,13 . Unexpectedly, among non‐MALT lymphoma, almost 30% of patients had diffuse large‐cell lymphoma.…”
Section: Discussionsupporting
confidence: 91%
“… 2 , 11 However, in other studies, especially from Asia, the incidence of MALT lymphoma was significantly higher, ranging from 66% to 82% of total orbital lymphoma. 1 , 3 , 12 , 13 Unexpectedly, among non‐MALT lymphoma, almost 30% of patients had diffuse large‐cell lymphoma. Only 7% of patients had mantle cell lymphoma and 4% of patients had follicular lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Ki-67 may show a lower proliferation index than usual in reactive follicles. 1 In this case, the patient had a very atypical involvement of the skin, with bilateral and symmetric eyelid nodules limiting the palpebral opening. The diagnosis of cutaneous follicle center lymphoma was confirmed on 2 skin biopsies with an extension assessment ruling out systemic or lymph node involvement.…”
Section: Discussionmentioning
confidence: 86%
“…FL belongs to low-grade lymphoma, while DLBCL and BL are high-grade lymphoma. Savino G et al 4 . in their studies from Asia found that the diffuse large B-cell lymphoma was the second subtype of orbital lymphoma, and more than half of the patient had systemic involvement, such as fever, night sweats, or weight loss.…”
Section: Discussionmentioning
confidence: 99%